Nitric oxide reduction with ethanol on palladium surfaces: a molecular beam study - Nagarajan, Sankaranarayanan; Thirunavukkarasu, Kandasamy; Gopinath, Chinnakonda S.; Counsell, Jonathan; Gilbert, Lee; Bowker, Michael (Journal of Physical Chemistry C, 2009)
Nitric oxide (NO) reduction with ethanol has been carried out with molecular beam instruments in order to understand the influence of ethanol blended gasoline on NO reduction. Maximum NO reduction and nitrogen production was observed between 500 and 600 K. Oxidation products, CO, CO(2), and H(2)O were also observed. Beam switching experiments have been performed between fuel-rich and fuel-lean compositions to demonstrate that the NO reduction can be managed under net oxidizing conditions on Pd surfaces. Nitrogen production only occurs transiently on the relatively clean Pd surface in the oxygen-rich condition due to slow build up and blockage of the reaction by surface oxygen atoms. This shows the need to maintain relatively oxygen free surfaces to manage NO reduction under net-oxidizing conditions by beam oscillation between fuel-rich and fuel-lean compositions.